Desenvolvimento de metodologia para separação de aminas quaternárias utilizando eletroforese não aquosa em microssistemas - Moreira, Roger Cardoso (2015)
This study describes the development of an analytical methodology for the separation of quaternary amines using nonaqueous electrophoresis microchips coupled with capacitively coupled contactless conductivity detection (C4D). Initially, preliminary experiments were performed to evaluate two electrokinetic modes for sample introduction on chip, known as gated and floating approaches. Gated injection showed repeatability slightly better than floating mode. In addition, it also provided better analytical responses on the C4D system. During the development of analytical methodology for NAME-C4D, the electrolyte composition was optimized to ensure satisfactory separations on electrophoresis microchips. The electrolyte composed of sodium deoxycholate (NaDCHA) at concentration of 10 mmol/L dissolved in a mixture of MeOH/ACN at the ratio 90:10 (v/v) exhibited separations with high efficiency and resolution above 1. Then, it was realized the optimization of potential injection, separation and detection parameters (frequency and amplitude). Running electrolyte was prepared in both DMSO and DMF, however, the use of a mixture containing MeOH/ACN provided best analytical performance. The best results were obtained with electrolyte containing 10% ACN and 90% MeOH. In addition, different electrolyte compositions were also evaluated, but the electrolyte containing NaDCHA offered results slightly better when compared to others. The optimization of running buffer allowed the separation of nine quaternary amines in electrophoresis channels with effective length of 7.0 cm with analysis time lower than 120 s. The peak resolution was higher than 1 and the calculated separation efficiencies ranged from 77.000 to 185.000 pratos/m. This excellent performance was achieved using NAME conditions under high electric fields. The developed methodology was used for the analysis of quaternary amines in samples containing high salinity levels through the standard addition method. Linear correlation coefficients were obtained up to 0,990 for eight quaternary amines. Lastly, the use of NAME-C4D allowed to observe a strong dependence of the detector response according to the carbon number of quaternary amine molecules.